TYPOLOGY OF CULTURES - Saitxanova Dinara Ruslanovna,; Xonboboyeva Shoira,; O’razova Dildora, (TADQIQOTLAR, 2026)
Abstract   Article  explores  the  concept  of  cultural  typology,  which  categorizes  cultures based  on  various  criteria  such  as  values,  norms,  practices,  and  social  structures.  It examines  different  frameworks  for  understanding  cultural  differences,  including Edward  T.  Hall's  high-context  and  low-context  cultures,  Geert  Hofstede's  cultural dimensions theory, and Fons Trompenaars' model of national culture differences. The article  also  discusses  the  implications  of  cultural  typology  for  intercultural communication, globalization, and international business. By analyzing how cultures can  be  classified  and  compared,  the  article  aims  to  provide  insights  into  the complexities of cultural interactions in an increasingly interconnected world.